The Effect of E-Service Quality and User Interface of PLN Mobile Application on Customer Satisfaction with Customer Trust as an Intervening Variable - Muhamad Sovian Ilham; Arthur Sitaniapessy; Joko Rizkie Widokarti (Universitas KH. Abdul Chalim Mojokerto, 2026)
The utilization of information technology through the PLN Mobile application is crucial for improving service quality and customer satisfaction. However, a thorough evaluation of the influence of e-service quality and user interface on customer satisfaction, especially in the UP3 Ambon region, is still needed. This study aims to analyze the direct effect of e-service quality and user interface on customer satisfaction, as well as the role of customer trust as an intervening variable. The research uses a quantitative approach, with data collected via a questionnaire from 60 respondents who are users of the PLN Mobile application. Data analysis was carried out using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS-SEM) approach. The results of the study indicate that e-service quality has a positive and significant effect on customer satisfaction as well as on customer trust. The user interface also has a positive and significant effect on both customer satisfaction and customer trust. Moreover, customer trust has been proven to have a positive and significant effect on customer satisfaction. The customer trust variable also acts as a significant mediating variable in the relationship between e-service quality and customer satisfaction, as well as between user interface and customer satisfaction. Thus, all research hypotheses (Ha1–Ha7) are accepted. These findings emphasize the importance of e-service quality and user interface in enhancing customer satisfaction and trust toward PLN’s digital services.